2012
DOI: 10.1109/tip.2011.2163895
|View full text |Cite
|
Sign up to set email alerts
|

On the Bandwidth of the Plenoptic Function

Abstract: Abstract-The plenoptic function (POF) provides a powerful conceptual tool for describing a number of problems in image/video processing, vision, and graphics. For example, image-based rendering is shown as sampling and interpolation of the POF. In such applications, it is important to characterize the bandwidth of the POF. We study a simple but representative model of the scene where band-limited signals (e.g., texture images) are "painted" on smooth surfaces (e.g., of objects or walls). We show that, in gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 19 publications
2
62
0
Order By: Relevance
“…In that respect we continue the work of several researchers [1,2,3,4]. In particular we use the formalism developed in a previous paper of ours [6] and expand it to include the case of depth cameras.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…In that respect we continue the work of several researchers [1,2,3,4]. In particular we use the formalism developed in a previous paper of ours [6] and expand it to include the case of depth cameras.…”
Section: Introductionmentioning
confidence: 87%
“…Having defined the scene geometry, we use the functional framework outlined in [2] in order to relates a point on the scene at x, z(x)) to a camera location t and pixel location v,…”
Section: The Disparity Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a function u ∈ PW Ω , the composition u • ψ is a time-warped function (Cochran and Clark, 1990), whose exact bandwidth formula is yet to be derived for the general case. A new bandwidth can be calculated for this type of function, called essential maximum frequency or the essential bandwidth, which is defined as the bandwidth where most of the signal energy resides (Bergner et al, 2006, Do et al, 2012 …”
Section: Direct Reconstruction Algorithms For Inputs Encoded With Idementioning
confidence: 99%
“…We know that the Fourier transform of is given by (28) where denotes the Fourier transform of the field , and the operation denotes convolution with respect to . From the structure of the Fourier transform we can argue as in [30] that the effective bandwidth of is given by (29) We now study how the Fourier transform of the observed signal gets modified by a slight deviation from the piecewise affine trajectory. Suppose the trajectory is given by (30) Let denote the maximum low-pass bandwidth of all .…”
Section: Appendix Bandwidth Of Time-warped Signalmentioning
confidence: 99%